Analisis Literasi SAINS Buku Teks Tematik Kurikulum 2013 Kemendikbud Tahun 2018 Muatan Pelajaran IPA SD - Yunita Apriani; Endang Widi Winarni; Irwan Koto (UNIB Press, 2023)
This study aims to describe aspects of scientific literacy; 1) Science as the body of knowledge in the science textbooks of grade IV, V, and VI students; 2) Science as a way of investigating science textbooks for grade IV, V, and VI students; 3) Science as a way of thinking in science textbooks for grade IV, V, and VI students; 4) The interaction of science, technology, society, and the environment in the science textbooks of grade IV, V, and VI students. This type of research is descriptive research. The subjects in this study were high class students. The object of this research is the textbooks of grade IV, V, and VI elementary school. The research data was calculated the average value of each expert and then the percentage was calculated according to each aspect of scientific literacy analyzed. The results of the first study show that the indicator presents the concepts of the number of occurrences of 6 with a percentage of 100%. The second aspect shows the largest number of appearances compared to books of class IV and VI. The science aspect as a way of thinking shows the largest number of occurrences compared to books of grades V and VI. the third aspect is deductive and inductive reasoning, skepticism and criticism, and various ways of understanding the natural world. The last aspect shows the largest number of appearances compared to books of class IV and V. Indicators Describe the usefulness of science and technology for society.